2021
DOI: 10.18203/2320-1770.ijrcog20213861
|View full text |Cite
|
Sign up to set email alerts
|

Study of comparison of maternal and fetal outcomes in spontaneous labour and induced labour

Abstract: Background: There has been consistent proportionate increase in the cases of induction of labor, but both maternal and neonatal effects of it remain poorly analysed previously. The present study was undertaken with the objective of comparison of maternal and fetal outcomes between groups of patients undergoing induction of labor and those having spontaneous labor.Methods: In this comparative prevalence study, the participants selected by predefined criteria were divided into 2 groups on the basis of progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Normal birth weight and low birth weight neonates are more likely to be delivered vaginally irrespective of whether labor is induced or spontaneous. 31 Advanced maternal age years is a significant risk factor for caesarean delivery. 32 Gondwe et al in 2019 found maternal age beyond 25 years to significantly increase the risk of caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Normal birth weight and low birth weight neonates are more likely to be delivered vaginally irrespective of whether labor is induced or spontaneous. 31 Advanced maternal age years is a significant risk factor for caesarean delivery. 32 Gondwe et al in 2019 found maternal age beyond 25 years to significantly increase the risk of caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%